Ability of donkey sperm to tolerate cooling: Effect of extender base and removal of seminal plasma on sperm parameters and fertility rates in mares - Gobato, Mariana L. M.; Segabinazzi, Lorenzo G. T. M.; Scheeren, Verônica F. C.; Bandeira, Rafael S.; Freitas-Dell'Aqua, Camila P.; Dell'Aqua, José A.; Papa, Frederico O. (Frontiers in Veterinary Science, 2022)
Artificial insemination using cooled-transported semen has marked importance in equine breeding programs around the world, and the high value of mules has generated avid interest in donkey semen biotechnology. However, donkey semen cools poorly in commercially available equine extenders. Therefore, this study aimed to develop approaches to improve the ability of donkey semen to tolerate cooling. Ejaculates of seven donkeys (n = 21) were cooled at 5°C for 48 h in three different extenders (milk-based, SM; sodium caseinate-based, SC; or egg yolk-based, EY) in the presence or absence of seminal plasma (centrifugation, C). Sperm motility, plasma membrane integrity (PMI), plasma membrane stability (PMS), mitochondrial membrane potential (HMMP), intracellular hydrogen peroxide (H2O2), and intracellular superoxide (O2−) were assessed before, 24 h, and 48 h post-cooling. In addition, 15 mares (163 estrous cycles) were randomly inseminated with semen from two jacks (Jack 1, n = 90; Jack 2, n = 73) previously cooled for 24 h under one of the treatments (SM, SC, EY, SM-C, SC-C, or EY-C). Groups EY, SC-C, and EY-C (P < 0.05) demonstrated superior sperm analytical parameters to SM at 24 and 48 h. Centrifugation positively affected sperm analytical parameters in cooled donkey semen extended in SM and SC (P < 0.05). Mares bred with semen extended in SC (67%, 18/27), SC-C (89%, 24/27), EY (89%, 25/28), or EY-C (74%, 20/27) had significantly greater conception rates than mares bred with SM (33%, 9/27; P < 0.05). Mares bred with SM-C had intermediate conception rates (59%, 16/27). In conclusion, SC and EY improved the cooling ability and fertility of donkey semen in horse mares, and centrifugation positively affected donkey semen extended in SM.